2020
DOI: 10.3390/su12041446
|View full text |Cite
|
Sign up to set email alerts
|

Linking Corporate Environmental Performance to Financial Performance of Pakistani Firms: The Roles of Technological capability and Public awareness

Abstract: This research investigates the corporate environmental performance (CEP) literature toward its financial performance of the firm. CEP is defined as the exercise and practices of companies to choose sensible measures to save and develop environment-friendly green activities. The influence of CEP on the financial performance of the firm via technological capability was examined. Furthermore, public awareness was hypothesized to moderate the impact of CEP on technological capability indicating moderation mediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 93 publications
0
13
1
Order By: Relevance
“…Second, researchers have tested the effect of relationship capabilities on entrepreneurial performance through GTS and ECS (Li, Qiao, Cui, & Wang, 2020). In the manufacturing firms of Pakistan, Wu, Ullah, and Shah (2020) found an indirect effect of corporate EP on financial performance, that is, the effect of strengthening technological capability; however, there is no empirical evidence that supports the direct association between PES and firm performance rather than through the significant mediating role of technological eco‐innovation (Ryszko, 2016). Third, contextually, these links have not been assessed in the context of Pakistan (Aslam, Rashid, Wahla, & Tahira, 2019; Chen, Daugherty, & Landry, 2009; Li, Qiao, Cui, & Wang, 2020; Spillan, McGinnis, Kara, & Yi, 2013; Zahid, 2016).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Second, researchers have tested the effect of relationship capabilities on entrepreneurial performance through GTS and ECS (Li, Qiao, Cui, & Wang, 2020). In the manufacturing firms of Pakistan, Wu, Ullah, and Shah (2020) found an indirect effect of corporate EP on financial performance, that is, the effect of strengthening technological capability; however, there is no empirical evidence that supports the direct association between PES and firm performance rather than through the significant mediating role of technological eco‐innovation (Ryszko, 2016). Third, contextually, these links have not been assessed in the context of Pakistan (Aslam, Rashid, Wahla, & Tahira, 2019; Chen, Daugherty, & Landry, 2009; Li, Qiao, Cui, & Wang, 2020; Spillan, McGinnis, Kara, & Yi, 2013; Zahid, 2016).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Few studies investigated the impact of ES and FFP and found mixed findings (Rehman et al, 2020). A case in point, some studies found the ES has a positive impact on FFP by assisting firms in achieving a competitive advantage, environmental innovation, improving operational efficiency, minimizing cost, achieving legitimacy, and license to operate (Gupta & Gupta, 2020; Wu & Ullah, 2020). However, in contrast, few studies noted that ES has no or negative impact on FFP as eco and environment‐friendly manufacturing processes require the latest and cleaner technologies, which has a cost with no immediate return on the profitability of the firm (Grewatsch & Kleindienst, 2017; Hang et al, 2018; Saleh et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past few decades, academia and industry have substantially shifted their attention to climate change, carbon emission, and other environment‐related issues (Gupta & Gupta, 2020; Wu & Ullah, 2020). Consequently, the question of what pushes firms to disclose information related to climate and sustainability issues has emerged as an enticing topic for both researchers and practitioners (Galpin et al, 2015; Linnenluecke & Griffiths, 2013; Soytas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This study’s findings do not support the indirect effect of employee voice between high-performance work systems and organizational performance. By using a 1,491 sample of observations, Wu et al ’s (2020) findings show that through reinforcing technological capability through content analysis, EP indirectly affects financial performance. Bhatti et al ’s (2021) findings demonstrate, in the context of Pakistan, the significant and predictive role of learning style and training content towards EP.…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%